Proteomic Response of Hordeum vulgare cv. Tadmor and Hordeum marinum to Salinity Stress: Similarities and Differences between a Glycophyte and a Halophyte - Maršálová, Lucie; Vítámvás, Pavel; Hynek, Radovan; Prášil, Ilja T.; Kosová, Klára (Frontiers in Plant Science, 2016)
Response to a high salinity treatment of 300 mM NaCl was studied in a cultivated barley Hordeum vulgare Syrian cultivar Tadmor and in a halophytic wild barley H. marinum. Differential salinity tolerance of H. marinum and H. vulgare is underlied by qualitative and quantitative differences in proteins involved in a variety of biological processes. The major aim was to identify proteins underlying differential salinity tolerance between the two barley species. Analyses of plant water content, osmotic potential and accumulation of proline and dehydrin proteins under high salinity revealed a relatively higher water saturation deficit in H. marinum than in H. vulgare while H. vulgare had lower osmotic potential corresponding with high levels of proline and dehydrins. Analysis of proteins soluble upon boiling isolated from control and salt-treated crown tissues revealed similarities as well as differences between H. marinum and H. vulgare. The similar salinity responses of both barley species lie in enhanced levels of stress-protective proteins such as defense-related proteins from late-embryogenesis abundant family, several chaperones from heat shock protein family, and others such as GrpE. However, there have also been found significant differences between H. marinum and H. vulgare salinity response indicating an active stress acclimation in H. marinum while stress damage in H. vulgare. An active acclimation to high salinity in H. marinum is underlined by enhanced levels of several stress-responsive transcription factors from basic leucine zipper and nascent polypeptide-associated complex families. In salt-treated H. marinum, enhanced levels of proteins involved in energy metabolism such as glycolysis, ATP metabolism, and photosynthesis-related proteins indicate an active acclimation to enhanced energy requirements during an establishment of novel plant homeostasis. In contrast, changes at proteome level in salt-treated H. vulgare indicate plant tissue damage as revealed by enhanced levels of proteins involved in proteasome-dependent protein degradation and proteins related to apoptosis. The results of proteomic analysis clearly indicate differential responses to high salinity and provide more profound insight into biological mechanisms underlying salinity response between two barley species with contrasting salinity tolerance.